1998
DOI: 10.1890/1051-0761(1998)008[0469:giaepi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Intensity and Ecosystem Processes in a Northern Mixed-Grass Prairie, Usa

Abstract: The objective of this study was to evaluate for an 8‐yr period the ecosystem‐level impacts of no grazing vs. sustained moderate and heavy cattle grazing in terms of: (1) plant species basal cover, density, and composition; (2) aboveground net primary production (ANPP), N content of ANPP (ANPP‐N), belowground net primary production (BNPP), and N content of BNPP (BNPP‐N); (3) litter and root decomposition and N loss; and (4) soil C, total soil N, and net in situ soil N mineralization. Moderate and heavy grazing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
103
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(122 citation statements)
references
References 43 publications
15
103
2
2
Order By: Relevance
“…Livestock grazing is a pivotal issue affecting plant growth, species diversity and soil carbon accumulation in grasslands (Olff and Ritchie, 1998;Watkinson and Ormerod, 2001;Piñeiro et al, 2010;McSherry and sity. For carbon sequestration, some studies found that grazing exclusion facilitated vegetation recovery, increased plant productivity and thus enhance soil carbon stocks in degraded grasslands (Biondini et al, 1998;McIntosh and Allen, 1998;Li et al, 2008;Mekuria et al, 2007;Mekuria and Veldkamp, 2012;Xiong et al, 2014). Others, however, reported no change (McNaughton et al, 1998;Pucheta et al, 2004) or even decline of carbon stocks in grasslands (Schuman et al, 1999;Leriche et al, 2001;Frank et al, 2002;Wienhold et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Livestock grazing is a pivotal issue affecting plant growth, species diversity and soil carbon accumulation in grasslands (Olff and Ritchie, 1998;Watkinson and Ormerod, 2001;Piñeiro et al, 2010;McSherry and sity. For carbon sequestration, some studies found that grazing exclusion facilitated vegetation recovery, increased plant productivity and thus enhance soil carbon stocks in degraded grasslands (Biondini et al, 1998;McIntosh and Allen, 1998;Li et al, 2008;Mekuria et al, 2007;Mekuria and Veldkamp, 2012;Xiong et al, 2014). Others, however, reported no change (McNaughton et al, 1998;Pucheta et al, 2004) or even decline of carbon stocks in grasslands (Schuman et al, 1999;Leriche et al, 2001;Frank et al, 2002;Wienhold et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In North America, medium levels of grazing by bison (Hartnett et al 1996;Collins et al 1998) and cattle (Collins 1987) increased species diversity on tallgrass prairie, and medium grazing by cattle increased plant diversity on mixedgrass prairie (Biondini et al 1998) and shortgrass steppe (Milchunas et al 1990(Milchunas et al ,1992Hart 2001). In contrast, very heavy grazing that removed 90% of aboveground biomass reduced species diversity on mixed-grass prairie (Biondini et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is hard to find intact reference sites for grazing studies as most grasslands experience disturbances. Finally, although primary knowledge of light to moderate grazing impacts on mixed grasslands in many other regions is known [28][29][30], the impacts of grazing on this area have not been quantitatively measured and our knowledge about the characteristics of grasslands in this area is very limited.…”
Section: Introductionmentioning
confidence: 99%